Thioglycolic acid oxidation by N, N′-phenylenebis(salicylideneiminato)manganese(III) in DMSO/H2O: Effects of sodium dodecylsulfate and cetyltrimethylammonium bromide - Ismaila Ibrahim; Sulaiman O. Idris; Ibrahim Abdulkadir; David A. Onu (Results in Chemistry, 2022)
Thioglycolic acid (TSH) oxidation by N,N’-phenylenebis(salicylideneiminato)manganese(III), [Mn(salphen)]+ was carried out in DMSO:H2O (1:4) at 32 ± 1 °C. The reaction displayed first order kinetics in each reactant, acid invariant and zero Brønsted-Debye salt effect. Activation data were computed such as ΔHǂ = +40.58 kJ mol−1, ΔSǂ = −164.40 J mol−1 K−1, ΔGǂ = +90.72 kJ mol−1, Ea = +43.12 kJ mol−1. The critical micelle concentrations of sodium dodecylsulfate (SDS) and cetyltrimethylammonium bromide (CTAB) were obtained in water and [Mn(salphen)]+ reaction media as 8.0 × 10−3 and 2.8 × 10−4 mol dm−3, 2.0 × 10−3 and 4.0 × 10−4 mol dm−3 respectively. The reaction was catalyzed by SDS and CTAB and an application of Piszkiewicz model evaluated the data by specifying the presence of pre-micellar aggregates with strong electrostatic and hydrophobic connections between [Mn(salphen)]+ and the pre-micellar aggregates of the surfactants.